The Impact of Furniture Industry CV. Kalingga Jati Furniture on the Socio-Economic Life of the Jepara Community 2005 – 2020 - Itsna Fahitna; Ilyas Ilyas (Criksetra: Jurnal Pendidikan Sejarah, 2023)
The industrial sector has an important role in economic development, especially in rural areas.. One of the industries in Jepara that has been developed is the wood industry. On this basis, the problem of this research is how the impact of the CV Furniture industry. Kalingga Teak Furniture to the socio-economic community of Jepara (2005-2020). The purpose of this study is to explain the development of the socio-economic life of the Jepara people (2005-2020) for the existence of CV. Kalinga Teak Furniture. This study uses historical methods, namely the heuristic stage, source criticism, interpretation, and historiography. The results of the research show that the growth and development of the CV Furniture industry. Kalingga Teak Furniture has an impact on the lives of the surrounding community. The company has a positive impact on society. The positive impacts include opening business opportunities thereby reducing unemployment and increasing public awareness of education. Furniture industry CV. Kalingga Teak Furniture can have an impact on improving the economy of the Jepara people because the company's presence can absorb a wide workforce.